N-Acetylcysteine causes analgesia in a mouse model of painful diabetic neuropathy. (January 2020) - Notartomaso, Serena; Scarselli, Pamela; Mascio, Giada; Liberatore, Francesca; Mazzon, Emanuela; Mammana, Santa; Gugliandolo, Agnese; Cruccu, Giorgio; Bruno, Valeria; Nicoletti, Ferdinando; Battaglia, Giuseppe
N-Acetylcysteine, one of the most prescribed antioxidant drugs, enhances pain threshold in rodents and humans by activating mGlu2 metabotropic glutamate receptors. Here, we assessed the analgesic activity of N-acetylcysteine in the streptozotocin model of painful diabetic neuropathy and examined the effect of N-acetylcysteine on proteins that are involved in mechanisms of nociceptive sensitization. Mice with blood glucose levels ≥250 mg/dl in response to a single intraperitoneal (i.p.) injection of streptozotocin (200 mg/kg) were used for the assessment of mechanical pain thresholds. Systemic treatment with N-acetylcysteine (100 mg/kg, i.p., either single injection or daily injections for seven days) caused analgesia in diabetic mice. N-acetylcysteine-induced analgesia was abrogated by theSx c − inhibitors, sulfasalazine (8 mg/kg, i.p.), erastin (30 mg/kg, i.p.), and sorafenib (10 mg/kg, i.p.), or by the mGlu2/3 receptor antagonist, LY341495 (1 mg/kg, i.p.). Repeated administrations of N-acetylcysteine in diabetic mice reduced ERK1/2 phosphorylation in the dorsal region of the lumbar spinal cord. The analgesic activity of N-acetylcysteine was occluded by the MEK inhibitor, PD0325901 (25 mg/kg, i.p.), the TRPV1 channel blocker, capsazepine (40 mg/kg, i.p.), or by a cocktail of NMDA and mGlu5 metabotropic glutamate receptor antagonists (memantine, 25 mg/kg, plus MTEP, 5 mg/kg, both i.p.). These findings offer the first demonstration that N-acetylcysteine relieves pain associated with diabetic neuropathy and holds promise for the use of N-acetylcysteine as an add-on drug in diabetic patients.